The Language of Inequality: Evidence Economic Inequality Increases Wealth Category Salience. (August 2022) - Peters, Kim; Jetten, Jolanda; Tanjitpiyanond, Porntida; Wang, Zhechen; Mols, Frank; Verkuyten, Maykel
There is evidence that in more economically unequal societies, social relations are more strained. We argue that this may reflect the tendency for wealth to become a more fitting lens for seeing the world, so that in economically more unequal circumstances, people more readily divide the world into "the haves" and "have nots." Our argument is supported by archival and experimental evidence. Two archival analyses reveal that at times of greater inequality, books in the United Kingdom and the United States and news media in English-speaking countries were more likely to mention the rich and poor. Three experiments, two preregistered, provided evidence for the causal role of economic inequality in people's use of wealth categories when describing life in a fictional society; effects were weaker when examining real economic contexts. Thus, one way in which inequality changes the world may be by changing how we see it.